The Impact of Linked Administrative Data on Community Development of Integrated Mental Health Hubs: a Case Study - Parker, Naomi; Salt, Valerie; Scott, Allison N; Scott, Cathie; Lau, Jason (International Journal of Population Data Science, 2018)
Introduction Increasingly, communities are designing and implementing contextualized approaches to integrated service delivery. Having communities in the lead is critical to successful design and implementation. However, how do researchers work with communities to ensure accurate contextual interpretations of linked administrative data? Objectives and Approach PolicyWise for Children & Families has been working with communities to create a framework and assist in the implementation of integrated Community-based Mental Health Service Hubs for youth ages 11-24. The approach used to support these communities included multiple sources of data to highlight the need for youth specific mental health care, integrated service delivery and the opportunity for system transformation. This included, but wasn’t limited to, a qualitative environmental scan and individual-level linked administrative data from PolicyWise’s Child and Youth Data Lab. Results The goal of presenting the qualitative and quantitative data summaries was to inform community-led design and implementation of the Mental Health Service Hubs. This presentation describes the constructive interplay of community context, qualitative literature and linked administrative data. Community context and the qualitative environmental scan assisted community members in interpreting the administrative data. Conclusion/Implications This applied project provides an example of how community members contextualize information from linked administrative data and environmental scan findings to influence program development. The implications of this is that data can reinforce or reshape what communities know about service use and impact how they proceed with planning.